Estimating demand for theileriosis vaccines - Mukhebi, A.W.; Williams, T. (International Livestock Research Institute, 1999)
This paper first describes demand and supply for a vaccine, and looks into demand and supply relationship. It then discusses other determinants of demand and supply for a vaccine. The method and preliminary results for estimating potential demand are also discussed and future research needs summarised.